2D Layered Double Hydroxides for Oxygen Evolution Reaction: From Fundamental Design to Application. Issue 17 (3rd March 2019) - Lv, Lin; Yang, Zhaoxi; Chen, Kun; Wang, Chundong; Xiong, Yujie
Abstract: The oxygen evolution reaction (OER) has aroused extensive interest from materials scientists in the past decade by virtue of its great significance in the energy storage/conversion systems such as water splitting, rechargeable metal–air batteries, carbon dioxide (CO2 ) reduction, and fuel cells. Among all the materials capable of catalyzing OER, layered double hydroxides (LDHs) stand out as one of the most effective electrocatalysts owing to their compositional and structural flexibility as well as the tenability and the simplicity of their preparation process. For this reason, numerous efforts have been dedicated to adjusting the structure, forming the well‐defined morphology, and developing the preparation methods of LDHs to promote their electrocatalytic performance. In this article, recent advances in the rational design of LDH‐based electrocatalysts toward OER are summarized. Specifically, various tactics for the synthetic methods, as well as structural and composition regulations of LDHs, are further highlighted, followed by a discussion on the influential factors for OER performance. Finally, the remaining challenges to investigate and improve the catalyzing ability of LDH electrocatalysts are stated to indicate possible future development of LDHs. Abstract : Layered double hydroxides (LDHs) are among the most effective electrocatalysts for the oxygen evolution reaction (OER) owing to their compositional and structural flexibility, the tenability and the simplicity of their preparation. Recent advances in the rational design of LDH‐based electrocatalysts toward OER are summarized, with a discussion on various synthetic tactics, structural and compositional regulations, and influential factors.